2023
DOI: 10.1111/liv.15801
|View full text |Cite
|
Sign up to set email alerts
|

Liver stiffness as a cornerstone in heart disease risk assessment

Joost Boeckmans,
Laurent Sandrin,
Christian Knackstedt
et al.

Abstract: Metabolic dysfunction‐associated steatotic liver disease (MASLD) typically presents with hepatic fibrosis in advanced disease, resulting in increased liver stiffness. A subset of patients further develops liver cirrhosis and hepatocellular carcinoma. Cardiovascular disease is a common comorbidity in patients with MASLD and its prevalence is increasing in parallel. Recent evidence suggests that especially liver stiffness, whether or not existing against a background of MASLD, is associated with heart diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 149 publications
(287 reference statements)
0
2
0
Order By: Relevance
“…Regardless of the classification scheme, an elevated liver stiffness in patients with either known steatotic liver disease or the presence of metabolic risk factors should trigger consideration for the evaluation of underlying cardiovascular disease [35]. As the population of patients with metabolic-related liver disease grows, ultrasound elastography evaluation of the liver will become more common, and it is essential that clinicians caring for these patients in the perioperative arena understand the significance of the relationship between an elevated liver stiffness and underlying cardiovascular disease.…”
Section: Mafld/masldmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the classification scheme, an elevated liver stiffness in patients with either known steatotic liver disease or the presence of metabolic risk factors should trigger consideration for the evaluation of underlying cardiovascular disease [35]. As the population of patients with metabolic-related liver disease grows, ultrasound elastography evaluation of the liver will become more common, and it is essential that clinicians caring for these patients in the perioperative arena understand the significance of the relationship between an elevated liver stiffness and underlying cardiovascular disease.…”
Section: Mafld/masldmentioning
confidence: 99%
“…The interaction between heart disease and liver disease is complex. Both share many risk factors, and several studies have shown that heart disease often accompanies elevated liver stiffness [35,[40][41][42]. A recent study evaluated the presence of subclinical heart disease in patients with non-advanced non-alcoholic fatty liver disease (NAFLD) [43].…”
Section: The Hepatic Cardiac Axismentioning
confidence: 99%